Introducing Modern Education Curriculum into Corporate Training for Real Estate Agency Employees - K, Pavithra K (Journal of Educational Research and Policies, 2025)
This study aims to develop a comprehensive framework for implementing modern educational programs in real estate agencies' corporate training. The research employs a multidisciplinary approach, integrating theories from real estate economics, human capital theory, organizational behavior, and andragogy. Methods include systematic literature review, mathematical modeling of competencies, and application of change management theories. Key results demonstrate the effectiveness of adaptive learning systems based on machine learning algorithms and cognitive modeling, integrated with immersive technologies and microlearning. The study proposes a multi-level competency taxonomy and a strategy for program implementation, considering organizational, technological, and human factors. Conclusions emphasize the transformative nature of modern educational programs in real estate agencies, highlighting the need for continuous adaptation. This research contributes to the field by providing a novel, integrated approach to corporate learning in the real estate sector, bridging the gap between educational technology advancements and industry-specific requirements.